Exosomes derived from umbilical cord mesenchymal stem cells alleviate viral myocarditis through activating AMPK/mTOR‐mediated autophagy flux pathway. Issue 13 (18th May 2020) - Gu, Xiaohong; Li, Yuechun; Chen, Kaixin; Wang, Xingang; Wang, Zhongyu; Lian, Hao; Lin, Yuanzheng; Rong, Xing; Chu, Maoping; Lin, Jiafeng; Guo, Xiaoling
Abstract: Human umbilical cord mesenchymal stem cell‐derived exosomes (hucMSC‐exosomes) have been implicated as a novel therapeutic approach for tissue injury repair and regeneration, but the effects of hucMSC‐exosomes on coxsackievirus B3 (CVB3)‐induced myocarditis remain unknown. The object of the present study is to investigate whether hucMSC‐exosomes have therapeutic effects on CVB3‐induced myocarditis (VMC). HucMSC‐exosomes were identified using nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM) and Western blot. The purified hucMSC‐exosomes tagged with PKH26 were tail intravenously injected into VMC model mice in vivo and used to administrate CVB3‐infected human cardiomyocytes (HCMs) in vitro, respectively. The effects of hucMSC‐exosomes on myocardial pathology injury, proinflammatory cytokines and cardiac function were evaluated through haematoxylin and eosin (H&E) staining, quantitative polymerase chain reaction (qPCR) and Doppler echocardiography. The anti‐apoptosis role and potential mechanism of hucMSC‐exosomes were explored using TUNEL staining, flow cytometry, immunohistochemistry, Ad‐mRFP‐GFP‐LC3 transduction and Western blot. In vivo results showed that hucMSC‐exosomes (50 μg iv) significantly alleviated myocardium injury, shrank the production of proinflammatory cytokines and improved cardiac function. Moreover, in vitro data showed that hucMSC‐exosomes (50 μg/mL) inhibited the apoptosis of CVB3‐infected HCM through increasing pAMPK/AMPK ratio and up‐regulating autophagy proteins LC3II/I, BECLIN‐1 and anti‐apoptosis protein BCL‐2 as well as decreasing pmTOR/mTOR ratio, promoting the degradation of autophagy flux protein P62 and down‐regulating apoptosis protein BAX. In conclusion, hucMSC‐exosomes could alleviate CVB3‐induced myocarditis via activating AMPK/mTOR‐mediated autophagy flux pathway to attenuate cardiomyocyte apoptosis, which will be benefit for MSC‐exosome therapy of myocarditis in the future.